Diet and Nutritional Interventions with the Special Role of Myo-Inositol in Gestational Diabetes Mellitus Management. An Evidence-Based Critical Appraisal - Reyes-Muñoz, Enrique; Guardo, Federica D.; Ciebiera, Michal; Kahramanoglu, Ilker; Sathyapalan, Thozhukat; Lin, Li-Te; Shah, Mohsin; Karaman, Erbil; Fan, Shangrong; Zito, Gabriella; Noventa, Marco (Current Pharmaceutical Design, 2019)
Background: Gestational Diabetes Mellitus (GDM), defined as glucose intolerance with onset or first recognition during pregnancy, represents one of the most common maternal-fetal complications during pregnancy and it is associated with poor perinatal outcomes. To date, GDM is a rising condition over the last decades coinciding with the ongoing epidemic of obesity and Type 2 Diabetes Mellitus (T2DM). Objective: The aim of this review is to discuss the role of diet and nutritional interventions in preventing GDM with the explanation of the special role of myo-inositol (MI) in this matter. Methods: We performed an overview of the most recent literature data on the subject with particular attention to the effectiveness of diet and nutritional interventions in the prevention of GDM with the special role of MI. Results: Nutritional intervention and physical activity before and during pregnancy are mandatory in women affected by GDM. Moreover, the availability of insulin-sensitizers such as different forms of inositol has dramatically changed the scenario, allowing the treatment of several metabolic diseases, such as those related to glucose dysbalance. Although the optimal dose, frequency, and form of MI administration need to be further investigated, diet supplementation with MI appears to be an attractive alternative for the GDM prevention as well as for the reduction of GDM-related complications. Conclusions: More studies should be conducted to prove the most effective nutritional intervention in GDM. Regarding the potential effectiveness of MI, further evidence in multicenter, randomized controlled trials is needed to draw firm conclusions.
Keywords: diet